2012
DOI: 10.3899/jrheum.111441
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Temporomandibular Joint Arthritis in Children with Juvenile Idiopathic Arthritis

Abstract: TMJ arthritis was identified in a substantial proportion of children with JIA (43%) and affects all JIA categories. TMJ arthritis was present in some patients despite limited or otherwise quiescent disease and in the presence of concurrent systemic immunomodulatory therapy. Routine evaluation for TMJ arthritis by MRI is warranted for all children with JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
3
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 23 publications
6
98
3
6
Order By: Relevance
“…In a few previous studies (1,8,12), any degree of contrast enhancement of the joint tissue has been considered suggestive of active inflammatory disease. In the present study, mild or even moderate enhancement of the joint tissue was seen in all but one of the patients who had contrast intravenously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a few previous studies (1,8,12), any degree of contrast enhancement of the joint tissue has been considered suggestive of active inflammatory disease. In the present study, mild or even moderate enhancement of the joint tissue was seen in all but one of the patients who had contrast intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the temporomandibular joint (TMJ) has been reported in a high percentage of children with juvenile idiopathic arthritis (JIA), ranging from 17 to 93% depending on study design, JIA categories, diagnostic method and criteria used [1][2][3][4]. Left untreated, TMJ arthritis may lead to growth disturbances or destruction, which result in orofacial deformity [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, most long-term studies, including those using MRI as a diagnostic method, will find rates of TMJ pathology of around 30-45% [5,9,31,32]: Stoll et al [31] found signs of acute or chronic TMJ arthritis after a mean disease duration of 2.5 years in contrast-enhanced MRI in only 43% of 185 patients and Argyropoulou et al [32] found abnormal condyles after a mean disease duration of 7.3 years in 32% of 46 JIA patients with TMJ MRI and enhanced pannus in 45%.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Throughout the literature, several other clinical signs have been associated with TMJ arthritis ( Table 2).…”
Section: Clinical Signsmentioning
confidence: 99%